2021
DOI: 10.1021/acs.est.1c01135
|View full text |Cite
|
Sign up to set email alerts
|

Soil Organic Matter Characterization by Fourier Transform Ion Cyclotron Resonance Mass Spectrometry (FTICR MS): A Critical Review of Sample Preparation, Analysis, and Data Interpretation

Abstract: The biogeochemical cycling of soil organic matter (SOM) plays a central role in regulating soil health, water quality, carbon storage, and greenhouse gas emissions. Thus, many studies have been conducted to reveal how anthropogenic and climate variables affect carbon sequestration and nutrient cycling. Among the analytical techniques used to better understand the speciation and transformation of SOM, Fourier transform ion cyclotron resonance mass spectrometry (FTICR MS) is the only technique that has sufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
109
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(112 citation statements)
references
References 248 publications
3
109
0
Order By: Relevance
“…The number of identified formulas in Marine-influenced regions was comparable to that in remote North Atlantic Ocean regions (Gurganus et al, 2015;Wozniak et al, 2014), but lower than those in SEA-influenced and SA-influenced regions, suggesting that the complexity of sources and atmospheric processes in marine aerosols was lower for remote marine regions. In addition, the lower identified formulas for Marine-influenced regions may also reflect that the primary marine organic compounds do not ionize well in the ESI mode (Bianco et al, 2018;Wozniak et al, 2014) ( Bahureksa et al, 2021;Koch & Dittmar, 2006). In this study, we found that both AI mod,w and DBE/C w were higher in SEA-influenced and SA-influenced regions, suggesting compared to Marine-influenced regions, the Continental-influenced regions were characterized by relatively high aromaticity.…”
Section: General Molecular Characteristicsmentioning
confidence: 59%
See 1 more Smart Citation
“…The number of identified formulas in Marine-influenced regions was comparable to that in remote North Atlantic Ocean regions (Gurganus et al, 2015;Wozniak et al, 2014), but lower than those in SEA-influenced and SA-influenced regions, suggesting that the complexity of sources and atmospheric processes in marine aerosols was lower for remote marine regions. In addition, the lower identified formulas for Marine-influenced regions may also reflect that the primary marine organic compounds do not ionize well in the ESI mode (Bianco et al, 2018;Wozniak et al, 2014) ( Bahureksa et al, 2021;Koch & Dittmar, 2006). In this study, we found that both AI mod,w and DBE/C w were higher in SEA-influenced and SA-influenced regions, suggesting compared to Marine-influenced regions, the Continental-influenced regions were characterized by relatively high aromaticity.…”
Section: General Molecular Characteristicsmentioning
confidence: 59%
“…The intensity‐weight O/C (O/C w ) and DBE (DBE w ) were lower in Marine‐influenced regions than in SEA‐influenced and SA‐influenced regions (Table S2 in Supporting Information ), indicating a relatively lower oxidation and unsaturation level for Marine‐influenced regions. AI mod and DBE/C are two indicators widely used to represent the aromaticity of organic matter in natural environments (Bahureksa et al., 2021; Koch & Dittmar, 2006). In this study, we found that both AI mod, w and DBE/C w were higher in SEA‐influenced and SA‐influenced regions, suggesting compared to Marine‐influenced regions, the Continental‐influenced regions were characterized by relatively high aromaticity.…”
Section: Resultsmentioning
confidence: 99%
“…All these factors have been studied to some degree in river corridors, and advances in cheminformatics techniques can provide further insights specifically into the biotic and abiotic components of OM transformations. More specifically, Fudyma et al (2021) used the ultra-high mass resolution of Fourier transform ion cyclotron resonance mass spectrometry (FTICR-MS) data (Marshall et al, 1998;Bahureksa et al, 2021) to infer putative abiotic and abiotic transformations of OM in a river corridor system. This extended previously-developed cheminformatics techniques (e.g., Breitling et al, 2006;Danczak et al, 2020Danczak et al, , 2021 to include abiotic transformations.…”
Section: Introductionmentioning
confidence: 99%
“…Complex mixtures are key study objects in environmental and industrial applications, but their analysis remains challenging. [1][2][3][4] One of the most complex mixtures in natural ecosystems is dissolved organic matter (DOM). 5,6 DOM is a central intermediate of ecosystem metabolism and mirrors molecular imprints of interactions with its abiotic and biotic environment [7][8][9] , which form the basis for processes such as carbon sequestration and nutrient recycling.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 DOM is a central intermediate of ecosystem metabolism and mirrors molecular imprints of interactions with its abiotic and biotic environment [7][8][9] , which form the basis for processes such as carbon sequestration and nutrient recycling. 10,11 Despite significant advances in ultrahigh-resolution mass spectrometry (FTMS) 2,4 and nuclear magnetic resonance spectroscopy 12 , scientists still struggle to decode this information on the molecular level [13][14][15][16][17] , and novel approaches to identify distinct structures are required to translate molecular-level information into improved process understanding.…”
Section: Introductionmentioning
confidence: 99%